(untitled) (Journal of Economic Research & Business Administration, 2020)
This study examines aspects of the impact of the raw material orientation of the economy on maintaining its financial security in the short and long term. Relevance of this topic is given by crisis phenomena in the world and national economies, generated, first of all, by negative price conditions in the world raw materials market. It is precisely in the conditions of the crisis that all the problems existing in the state are most clearly manifested, the shortcomings of the system for ensuring the most important area of national security – financial, are revealed. During such periods, authorities should attach particular importance to the security issues of the state, organizations and citizens, develop effective tools to eliminate emerging threats or mitigate their consequences. The current state of the National Fund of the Republic of Kazakhstan activity has been analyzed in detail, since the dynamics of changes in the volumes of assets and the level of the fund’s profitability reflect how effectively the government’s work is organized in generation and using the state’s raw materials income, that ensures financial security for the country with a raw material focus. It is concluded that the solution to the problem of financial security of the Republic of Kazakhstan can be achieved only by consistently pursuing a policy to diversify the economy, which will lead to a reorientation of income derived from commodity exports.